The Brain Emotional Systems in Addictions: From Attachment to Dominance/Submission Systems - Giacolini, Teodosio; Conversi, David; Alcaro, Antonio (Frontiers in Human Neuroscience, 2021)
Human development has become particularly complex during the evolution. In this complexity, adolescence is an extremely important developmental stage, Adolescence is characterized by biological and social changes that create the prerequisites to psychopathological problems, including both substance and non-substance addictive behaviours. Central to the dynamics of the biological changes during adolescence are the synergy between sexual and neurophysiological development, which activates the motivational/emotional systems of Dominance/Submission. The latter are characterized by the interaction between the sexual hormones, the dopaminergic system and the stress axis (HPA). The maturation of these motivational/emotional systems requires the integration with the phylogenetically more recent Attachment/CARE Systems, which primarily have governed the subject’s relationships until puberty. The integration of these systems is particularly complex in the human species, due to the evolution of the process of competition related to sexual selection: from a simple fight between two individuals (of the same genus and species) to a struggle for the acquisition of a position in rank and the competition between groups. The latter is an important evolutionary acquisition and believed to be the variable that has most contributed to enhancing the capacity for cooperation in the human species. The interaction between competition and cooperation, and between competition and attachment, characterizes the entire human relational and emotional structure and the unending work of integration to which the BrainMind is involved. The beginning of the integration of the aforementioned motivational/emotional systems is currently identified in the prepubertal period, during the juvenile stage, with the development of the Adrenarche - the so-called Adrenal Puberty. This latter stage is characterized by a low rate of release of androgens, the hormones released by the adrenal cortex, which activate the same behaviours as those observed in the PLAY system. The Adrenarche and the PLAY system are biological and functional prerequisites of adolescence, a period devoted to learning the difficult task of integrating the phylogenetically ancient Dominance/Submission Systems with the newer Attachment/CARE Systems. These systems accompany very different adaptive goals which can easily give rise to mutual conflict and can in turn make the balance of the BrainMind precarious and vulnerable to mental suffering.